Chemical Studies on Capparis Spinosa Leaves - Hussein, Dheyaa, S.; Ghoneim, Gehan, A.; Raya, Mossad A. Abo; Khalil, Mona, M. (American Journal of Botany and Bioengineering, 2026)
This study was to determine the chemical, mineral content the total phenolic, flavonoid content and the antioxidant capacities of Capparis spinosa leaves in the Al-Ramadi area of the Anbar governorate. The chemical composition of capper leaves revealed that the moisture content of capper leaves was 10.42%, protein 13.76%, fat 2.48%, ash 18.47% fiber 29.59%, and carbohydrates, 54.87%. Capper leaves included high levels of calcium (Ca), magnesium (Mg), sodium (Na), iron (Fe), boron (B), zinc (Zn), manganese (Mn), and potassium (K). The corresponding values were 12380, 11196, 6003, 233.935, 195.77, 70.188, 53.979, and 28547 ppm. Furthermore, very low levels of copper (Cu), chromium (Cr), barium (Ba), cadmium (Cd), and cobalt (Co) were found in the samples (8.307, 8.056, 5.926, 2.058, 1.333, and 0.004 ppm, respectively). Total phenolic content and total flavonoid content were evaluated according to the Folin-Ciocalteu procedure, and a colorimetric method, respectively. Extracts capper leaves content was determined by using a high-performance liquid chromatography (HPLC)-UV method. Capper leaves had a total phenolic content of 44.79 mg gallic acid equivalent/gm. The flavonoid content was 20.06 mg QE/gm. Capper leaves had an antioxidant activity of 82.76%.